A coumarin-porphyrin FRET break-apart probe for heme oxygenase-1 - Walter,E; Ge,Y; Mason,J; Boyle,J; Long,N (Journal of the American Chemical Society, 2021)
Heme oxygenase-1 (HO-1) is a vital enzyme in humans that primarily regulates free heme concentrations. The overexpression of HO-1 is commonly associated with cardiovascular and neurodegenerative diseases including atherosclerosis and ischemic stroke. Currently, there are no known chemical probes to detect HO-1 activity, limiting its potential as an early diagnostic/prognostic marker in these serious diseases. Reported here are the design, synthesis, and photophysical and biological characterization of a coumarin–porphyrin FRET break-apart probe to detect HO-1 activity, Fe–L1. We designed Fe–L1 to “break-apart” upon HO-1-catalyzed porphyrin degradation, perturbing the efficient FRET mechanism from a coumarin donor to a porphyrin acceptor fluorophore. Analysis of HO-1 activity using Escherichia coli lysates overexpressing hHO-1 found that a 6-fold increase in emission intensity at 383 nm was observed following incubation with NADPH. The identities of the degradation products following catabolism were confirmed by MALDI-MS and LC–MS, showing that porphyrin catabolism was regioselective at the α-position. Finally, through the analysis of Fe–L2, we have shown that close structural analogues of heme are required to maintain HO-1 activity. It is anticipated that this work will act as a foundation to design and develop new probes for HO-1 activity in the future, moving toward applications of live fluorescent imaging.